Pendampingan Moderasi Beragama bagi Santriwati Rumah Tahfidz BUSTANQU Merjorsari Malang melalui Program Literasi Ayat-ayat Inklusif - Nur Hasan Nur Hasan; Arief Ardiansyah (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2025)
In the last decade, Indonesia has faced the problem of extremism and radicalism. The strengthening of these two ideologies is driven by a pattern of thinking that is exclusive, closed, and intolerant of religious texts. This radicalism and extremism ideology has infiltrated in various forms and modus operandi, ultimately targeting young people in Islamic boarding schools, universities, schools, and even tahfiz houses. This ideology is better known as the Salafi group, which understands Islam exclusively, textually, and intolerantly, because its understanding of the verses of the Quran is not deeply understood. This community service activity aims to address this by providing support to the Bustanqu Institute in Merjosari, Malang. The goal is to reduce intolerant attitudes toward religion and to help students understand the Quran through the Inclusive Verse Literacy Program. This community service method uses Participatory Action Research, which, in the future, is expected to create a community of students at the Bustanqu Tahfidz House with an inclusive and tolerant national and Islamic perspective. The results of this mentoring program include changes in the students of the Bustanqu Tahfidz House in their understanding of the Koran's verses in a deep, non-textual way, as well as visible changes in their attitudes toward being moderate, tolerant, and gentle in their religious life.